Permanensi Kawasan Masjid Raya Sabilal Muhtadin Banjarmasin - Daniel Alison; Rony Gunawan Sunaryo; Rully Damayanti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2023)
Title: The Permanence of Sabilal Muhtadin Great Mosque Area The area of the Great Mosque of Sabilal Muhtadin Banjarmasin was originally the location of